Can subjective mortality expectations and stated preferences explain varying consumption and saving behaviors among the elderly? - Martin Salm (Institute for the Study of Labor (IZA), 2006)
This study investigates how subjective mortality expectations and heterogeneity in time and risk preferences affect the consumption and saving behavior of the elderly. Previous studies find that the large wealth disparities observed among the elderly cannot be explained by differences in preferences. In contrast, this study identifies a strong relationship between answers to survey questions about time and risk preferences and consumption and saving behaviors. This paper uses data on information about preferences and subjective mortality expectations from the Health and Retirement Study merged with detailed consumption data from two waves of the Consumption and Activities Mail Survey. The main results are: 1) consumption and saving choices vary with subjective mortality rates in a way that is consistent with the life cycle model; 2) different answers to survey questions about time and risk preferences reflect differences in actual saving and consumption behavior; and 3) there is substantial heterogeneity in estimated time discount rates and risk aversion parameters.
urn:nbn:de:101:1-2008060652
Keywords: 330